PERANAN PENDIDIKAN KEPENDUDUKAN DAN LINKUNGAN llll)UP DALAM MENGATASI MASALAH KEPENDUDUKAN DI INDONESIA - Subardhy, Subardhy (Jurnal Cakrawala Pendidikan, 2016)
The population problelns in Indonesia basically selns fonn the high birth rate which causes the high speed of population growth. Unfortunatly, this can not meet their life-need supply : food, cloth, houses, facil ities for education, health, and emp)oynlent. Such condition brings Jow quality of ITIOst Indonesian population. In edition, the effort by tranmigration toi improve prosperity in some exten has not been succesful. This phenomenonl of population must be anticipated by carriying out an activity which changes this behavvior. The behaviorual changes can not happen without educational activity. Therefore, PKLH as an educational program to provide childern with understanding , awarness, atitude, and rational responible behavior, and to understand the relationship between population and environment in all of hUlnan aspects. The children who have PKLH education are -expected to be aware that birth is not Inerely a Inatter of but it can be pp]atned. Therefore, the fanlily size is not destiny, it can be also be human are also to be aware that a small is reasonable anda rational to the of social and their own Hife. Childern with PKLH are to be have their that preserves childern with PKLH will becolne who attitude toward sOlal1 norm and appy their The acceptenc